Proposta de um modelo de avaliação da sustentabilidade ambiental em cadeia de suprimentos: um estudo de caso - Magacho, Carolina Sales (2017)
The supply chain covers all activities related to the flow and transformation of products from the raw material in the extraction stage, to the final consumer. It also involves downstream and upstream information and transformation flows in the supply chain. The objective of this study is to evaluate the management of the environmental supply chain in the food industry and, as specific objectives: to develop and apply a specific methodology to select articles of scientific relevance in the field of sustainable supply chain; to develop and apply a specific methodology to know the methods of evaluation of sustainable supply chain management in high impact factor journals; and, through a case study, to develop a structured research methodology to evaluate the management of environmental supply chain in the food industry located in the state of Santa Catarina. With regard to the research methodology, a literature review was carried out in a structured form in twelve main steps, in addition to the case study, which occurred through the application of a methodology composed of seven constructs, namely: environmental management stage, supplier selection, supplier collaboration, supplier assessment, customer selection, customer collaboration, and customer assessment. With regard to the research results, the study made it possible to test and improve a specific research methodology, as well as to present an overview of the situation of the company studied, where it was diagnosed that, in relation to the construct denominated environmental management stage, the company presented a satisfactory average, which is due to legal issues and internal procedures it possesses. However, with respect to the constructs selection of suppliers, collaboration with suppliers, supplier evaluation, client selection, collaboration with customers, and customer evaluation, the company presented an unsatisfactory average. One may notice that the company performs environmental actions, aiming not to suffer the applicable sanctions, but actually due to a true concern with the environmental sustainability of the supply chain.